Massive Brain Swelling after Cranioplasty: A Case Report - Zhang, Xiaoyang; Pan, Baogen; Ye, Zhanying; Li, Zheng; Mo, Feng; Wang, Xiaoyan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background Cranioplasty is a common procedure in neurosurgery. It is usually performed following decompressive craniectomy (DC). However, complications may occur after the operation, such as massive brain swelling. Up to now, far too little attention has been given to this severe complication. We report one case of fatal cerebral swelling after cranioplasty and analyze the possible mechanism of this complication.Case Description The patient was a 40-year-old man who had a severe right basal ganglia cerebral hemorrhage and underwent DC ∼ 2 months before. One day before scheduled cranioplasty, a lumbar cerebrospinal fluid drainage was placed. The cranioplasty itself was uneventful. However, he gradually fell into a coma, and his right pupil was moderately dilated 20 hours after the surgery. A brain computed tomography (CT) scan indicated massive right cerebral edema with compressed right midbrain. The patient did not regain consciousness, and he remained quadriplegic.Conclusion It is necessary to increase awareness of complications of cranioplasty in high-risk patients. The lessons learned from this case include avoiding excessive drainage of cerebrospinal fluid. Patients with low-density lesions in the brain need to be treated with caution. Once the CT scan shows massive cerebral swelling, the patient has a poor prognosis.
Keywords: cranioplasty; malignant cerebral swelling; massive brain swelling; low-density lesions; decompressive craniectomy